(untitled) (Applied Biological Research, 2023)
The present study was aimed to assess the hepatoprotective effect of ethanolic extract of Garcinia gummi-gutta (GGE) fruit rind on acetaminophen-induced toxicity in a rat model and to explore the possible mechanism of action by assessing hepatic histopathology, serum biochemical parameters and expression of CYP2E1 gene in hepatic cells. The group I and 11 animals served as normal control and hepatotoxic control group, respectively; while group III, IV and V were administrated with GGE fruit-rind extract @ 50, 100 & 200 mg kg-1 orally, respectively, for 10 days. The group VI (positive control) received drug silymarin @ 100 mg kg-1 day-1 orally for 10 days. Hepatotoxicity was induced by single oral administration of acetaminophen (2 g kg-1) on 8th day. The results revealed that the extract produced dose-dependent hepatoprotective effect against acetaminophen-induced hepatic damage by improving the serum bio chemical profile towards the normal range. Histopathology of liver showed that pretreatment with fruit-rind extract attenuated the toxicant-induced hepatocellular necrosis and enhanced the regeneration of hepatic cells. The hepatic expression level of CYP2E1 gene was found down-regulated in a dose dependent manner in extract-treated group as compared to the normal control group. The study revealed remarkable hepatoprotective effect of GGE in acetaminophen-induced toxicity in rats through regeneration of hepatic cells and by decreasing the formation of reactive metabolite, NAPQ1 by modulation of CYP2E1 gene expression in liver.